Central nervous system involvement by multiple myeloma: A multi‐institutional retrospective study of 172 patients in daily clinical practice. Issue 6 (24th April 2016) - Jurczyszyn, Artur; Grzasko, Norbert; Gozzetti, Alessandro; Czepiel, Jacek; Cerase, Alfonso; Hungria, Vania; Crusoe, Edvan; Silva Dias, Ana Luiza Miranda; Vij, Ravi; Fiala, Mark A.; Caers, Jo; Rasche, Leo; et al.
Abstract : The multicenter retrospective study conducted in 38 centers from 20 countries including 172 adult patients with CNS MM aimed to describe the clinical and pathological characteristics and outcomes of patients with multiple myeloma (MM) involving the central nervous system (CNS). Univariate and multivariate analyses were performed to identify prognostic factors for survival. The median time from MM diagnosis to CNS MM diagnosis was 3 years. Thirty‐eight patients (22%) were diagnosed with CNS involvement at the time of initial MM diagnosis and 134 (78%) at relapse/progression. Upon diagnosis of CNS MM, 97% patients received initial therapy for CNS disease, of which 76% received systemic therapy, 36% radiotherapy and 32% intrathecal therapy. After a median follow‐up of 3.5 years, the median overall survival (OS) from the onset of CNS involvement for the entire group was 7 months. Untreated and treated patients had median OS of 2 and 8 months, respectively ( P < 0.001). At least one previous line of therapy for MM before the diagnosis of CNS disease and >1 cytogenetic abnormality detected by FISH were independently associated with worse OS. The median OS for patients with 0, 1 and 2 of these risk factors were 25 months, 5.5 months and 2 months, respectively ( P < 0.001). Neurological manifestations, not considered chemotherapy‐related, observed at any time after initial diagnosis of MM should raise a suspicion of CNS involvement. Although prognosis is generally poor, the survival of previously untreated patients and patients with favorable cytogenetic profile might be prolonged due to systemic treatment and/or radiotherapy. Am. J. Hematol. 91:575–580, 2016. © 2016 Wiley Periodicals, Inc.